Persepsi Komunitas Jogja K-Poper Tentang Gaya Hidup Korean Wave Dalam Chanel You Tube Sunnydahyein - Karina Novita Dewi; Bambang Sujarwadi (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
It is easy for the public to access information through various media, and one of these media is YouTube. With the ease of dissemination of information, the development of the Korean Wave in Indonesia is growing rapidly. Many young people are fond of various things about the Korean Wave and imitate the Korean Wave lifestyle. One of the content creators who provides information on Korean culture on YouTube is the SunnydahyeIn channel. This channel provides various information about Korean idols and also Korean lifestyle or culture. There are several lifestyle indicators, namely: (1) style of dress; (2) speaking style; and (3) consumption culture. This study aims to find out the perceptions of members of the Jogja K-poper community which were formed by exposure to information on Korean lifestyle and culture through the SunnydahyeIn YouTube channel, which led to a change in lifestyle within them. This study uses a qualitative research approach with descriptive methods. Data collection techniques were carried out through interviews, observation, and documentation. The results of this study indicate that the SunnydahyeIn YouTube media channel has a role in shaping the perceptions of Jogja K-Poper communication members on the Korean Wave lifestyle and Korean culture.